Intra-Aortic Balloon Pump Bridging to Heart Transplantation: Impact of the 2018 Allocation Change. (August 2020) - Huckaby, Lauren V.; Seese, Laura M.; Mathier, Michael A.; Hickey, Gavin W.; Kilic, Arman
Abstract : Background: This study evaluates the impact of the 2018 allocation policy change on outcomes of orthotopic heart transplantation (OHT) in patients bridged with intra-aortic balloon pumps (IABPs). Methods: Adult (≥18 years) patients undergoing OHT between 2013 and 2019 who were bridged with an IABP were stratified based on temporal relation to the policy change. Univariate analysis was used to compare baseline characteristics and postoperative outcomes. Multivariate Cox regression analysis was used to estimate risk-adjusted predictors of post-transplant mortality. Results: A total of 1342 (8.6%) OHT patients were bridged with an IABP during the study period. Rates of bridging with IABP to OHT increased significantly after the policy change (7.0% versus 24.9%, P <0.001). The mean recipient age was 54.1±12.1 years with 981 (73.1%) patients being male. Baseline characteristics were similar between the 2 groups whereas post–policy change patients spent fewer days on the waitlist (15 versus 35 days, P <0.001), had longer ischemic times (3.5 versus 3.0 hours, P <0.001), and received organs from a greater distance (301 versus 105 miles, P <0.001). By multivariable analysis, days on the waitlist (for every 30 days; odds ratio, 1.01 [95% CI, 1.00–1.02], P =0.031) and diabetes mellitus (odds ratio, 1.87 [95% CI, 1.16–3.02], P =0.011) emerged as significant predictors of post-transplant mortality. After the policy change, waitlisted patients requiring IABP support were more likely to survive to transplant (76.4 versus 89.8%, P <0.001). Conclusions: IABP utilization has increased over 3-fold since the 2018 policy change with improved waitlist outcomes and comparable post-OHT survival. Thus, bridging patients to OHT with IABPs appears to be an effective strategy in the current era. Abstract : Supplemental Digital Content is available in the text.